Meningkatkan Keterampilan Berpikir Kritis Dan Kerjasama Siswa Menggunakan Model Pantas DI SD - Husnul Khatimah; Noorhapizah . (CV. ITTC INDONESIA, 2023)
This study analyzes the low ability of critical thinking and student cooperation. This problem is due to one-way learning, they are not used to solving problems, students are used to learning individually or rarely in groups, so that learning becomes less interesting for them. Efforts to deal with these problems are using the PANTAS learning model. The purpose of this study was to analyze students' critical thinking skills and cooperation in the learning process. The type of research applied is Classroom Action Research, using qualitative methods. The subject here is the 5th grade students of SDN Alalak Utara 2 Banjarmasin. The results showed that students' critical thinking skills at the first meeting only reached 35% in the less critical category, experienced an increase in the fourth meeting to 90% in the very critical category. Cooperation at the first meeting only reached 40% in the less skilled category, then increased at the fourth meeting to 90% in the very skilled category. In conclusion, the use of the PANTAS learning model can improve students critical thinking skills and cooperation in the class.